Towards Calm Displays: Matching Ambient Illumination in Bedrooms - Kučera, Jan; Scott, James; Chen, Nicholas; Olivier, Patrick; Hodges, Steve (Proceedings of the ACM on Interactive, Mobile, Wearable and Ubiquitous Technologies, 2017)
We present a system for making emissive computer displays (LCDs) look like they are reflective, i.e. not emitting light but instead reflecting ambient light, an effect that we call a “calm display”. We achieve this effect by using a light sensor and a one-time calibration process to drive an algorithm which controls the display’s backlight intensity and gamma correction functionality to continually match the brightness and chromaticity of the ambient light. We present an experimental evaluation of our system, showing quantitatively that the color and brightness output by our system is perceptually close to that of a piece of paper under similar lighting conditions. We argue that calm displays can more easily fade into the background, and further that they are more suitable for environments such as bedrooms where glowing displays are often out-of-place. We validate these claims and more generally explore users’ perception of calm displays, through a field study of an LCD display deployed in participants’ bedrooms.